The relationship between eating patterns and physical activity with obesity among elementary school children: A case-control study - Lathifah, Ashma; Adnani, Hariza; Thi, Wor Mi (Jurnal Cakrawala Promkes, 2024)
In broad terms, eating patterns encompass three primary components: the type of food consumed, the frequency of eating occasions, and the portion sizes consumed. Schools are recognized as pivotal settings for initiatives aimed at preventing obesity, particularly given the potential for multifaceted interventions when addressing obesity and its associated health issues in childhood. These interventions may involve diverse strategies targeting dietary habits, physical activity levels, and broader environmental factors within the school setting. In local data between 2017 and 2020, the Province of Yogyakarta reported a 6.01% increase in the prevalence of obesity, with Yogyakarta City having the highest rate at 14.73%. This study aimed to investigate the connection between obesity in elementary school students and their eating habits and physical activity levels. This study uses a case-control methodology and is an analytical observational investigation. Purposive sampling was used in the sampling process, with 20 kids serving as the case group and 40 as the control group. Data was obtained using the formulas for physical activity, meal frequency, and 24-hour recall. The Chi-square test was used to examine the results. The results show the relationship between physical activity and eating patterns. Also, children with low physical activity have a 1.14 times greater risk of developing obesity than children who have moderate physical activity. The study's findings suggest a clear correlation between obesity dietary choices and physical activity levels. Effective management of an individual's weight necessitates involvement from their family in regulating their eating habits and encouraging physical exercise. Thus, it can be inferred that eating behaviors and levels of physical activity significantly contribute to the development and management of obesity.